Plurality of claims in cross-border traffic accidents.Commentary to the judgment of Court of Appeal of Madrid (Section 20th) of 30 September of 2019 - Espiniella Menéndez, Ángel (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The Judgment correctly concludes the application of Spanish law to the claims brought by the claimants. Perhaps a more exhaustive argument would have been possible in order to verify that in the case there are two very different kinds of claims. On the one hand, the direct claim of the injured person, whose rules in Article 9 of the Hague Convention of 1971 has a little role. On the other hand, a subrogation action by the insurer, excluded from the Convention and in which an equality of procedural arms between insurers reappears, and a principle of protection for the injured party as a weaker party disappears. Furthermore, the Judgment is a good example to expose some of the structural problems posed by the Hague Convention of 1971. The application of the law of the place of the accident is displaced by the law of vehicle registration, provided that all vehicles involved are registered in the same State. Precisely this concept of implication is the most doubtful in the Convention.